2010
DOI: 10.1007/s11663-010-9393-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Silicon in the (NaCl-KCl-NaF-SiO2) Molten Salt

Abstract: The electrochemical behavior of silicon was investigated in a molten salts system including saturation silicon dioxide. Silicon was electrodeposited and MoSi 2 was formed on the employed molybdenum working electrode by the diffusivities of silicon and the substrate metals. Transient electrochemical techniques such as cyclic voltammetry and chronoamperometry were used to study the reaction mechanism at the molybdenum electrode. Cyclic voltammograms showed the possibility of electrodeposition of Si at À0.64 V ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…This is larger than the value of 2.9×10 −5 cm 2 s −1 obtained by A. L. Bieber et al in NaF-KFNa 2 SiF 6 at 1123K, 19 while smaller than the value of 1.32×10 −3 cm 2 s −1 reported by Cai et al in NaCl-KCl-NaF-SiO 2 at 1073K. 30 The difference between the values can be explained by the temperature and molten salts media effects, which show up in the mass transfer velocity and the stability of silicon (IV) ion complex. As auxiliary proof of the irreversible process, a series of square wave voltammograms were obtained by varying the frequency as shown in Fig.…”
Section: Resultscontrasting
confidence: 55%
“…This is larger than the value of 2.9×10 −5 cm 2 s −1 obtained by A. L. Bieber et al in NaF-KFNa 2 SiF 6 at 1123K, 19 while smaller than the value of 1.32×10 −3 cm 2 s −1 reported by Cai et al in NaCl-KCl-NaF-SiO 2 at 1073K. 30 The difference between the values can be explained by the temperature and molten salts media effects, which show up in the mass transfer velocity and the stability of silicon (IV) ion complex. As auxiliary proof of the irreversible process, a series of square wave voltammograms were obtained by varying the frequency as shown in Fig.…”
Section: Resultscontrasting
confidence: 55%
“…21, the calculated diffusion coefficient of Si (IV) under the experimental condition is 2.2 × 10 −6 cm 2 • s −1 , which is slightly bigger than the value of 2.0 × 10 −6 cm 2 • s −1 in molten NaF-AlF 3 -volcanic rock. 19 Due to the effect of different temperature and molten salt media, the diffusion coefficient of Si (IV) in NaF-AlF 3 at 1233 K is smaller than the value of 2.9 × 10 −5 cm 2 • s −1 reported by A. L. Bieber et al in NaF-KF-Na 2 SiF 6 at 1123 K, 32 and smaller than the value of 1.32 × 10 −3 cm 2 • s −1 obtained by Z. Y. Cai et al in NaCl-KCl-NaF-SiO 2 at 1073 K. 33 The measurement of CV curve on a tungsten wire working electrode in 52.7 wt%NaF-47.3 wt%AlF 3 melt adding 5 wt% SiO 2 was performed at the same conditions. The obtained CV curve is shown Fig.…”
Section: Resultsmentioning
confidence: 54%
“…It was found that the under potential deposition peak was disappeared at 2nd scan with the same Mo working electrode. It seems that Mo becomes MoSi 2 after its cathodic scanning [28] and it doesn't decompose during anodic scanning. Hence, thus formed MoSi 2 wire was used as an innert working electrode throughout the CV experiment in this study.…”
Section: Methodsmentioning
confidence: 99%